Interpretation of Rubidium‐Based Perovskite Recipes toward Electronic Passivation and Ion‐Diffusion Mitigation. Issue 14 (25th February 2022) - Xu, Chenzhe; Chen, Xiwen; Ma, Shuangfei; Shi, Mingyue; Zhang, Suicai; Xiong, Zhaozhao; Fan, Wenqiang; Si, Haonan; Wu, Hualin; Zhang, Zheng; Liao, Qingliang; Yin, Wanjian; et al.
Abstract: Rubidium cation (Rb + ) addition is witnessed to play a pivotal role in boosting the comprehensive performance of organic–inorganic hybrid perovskite solar cells. However, the origin of such success derived from irreplaceable superiorities brought by Rb + remains ambiguous. Herein, grain‐boundary‐including atomic models are adopted for the accurate theoretical analysis of practical Rb + distribution in perovskite structures. The spatial distribution, covering both the grain interiors and boundaries, is thoroughly identified by virtue of synchrotron‐based grazing‐incidence X‐ray diffraction. On this basis, the prominent elevation of the halogen vacancy formation energy, improved charge‐carrier dynamics, and the electronic passivation mechanism in the grain interior are expounded. As evidenced by the increased energy barrier and suppressed microcurrent, the critical role of Rb + addition in blocking the diffusion pathway along grain boundaries, inhibiting halide phase segregation, and eventually enhancing intrinsic stability is elucidated. Hence, the linkage avalanche effect of occupied location dominated by subtle changes in Rb + concentration on electronic defects, ion migration, and phase stability is completely investigated in detail, shedding a new light on the advancement of high‐efficiency cascade‐incorporating strategies and perovskite compositional engineering. Abstract : Rb + ‐based perovskite recipes are widely adopted in a large amount of significant advancements regarding perovskite solar cells with several performance records. Combining seminal theoretical calculations with cutting‐edge experimental characterizations, the linkage avalanche effect of occupied location dominated by subtle changes in doping concentration on electronic defects, ion migration, and phase stability is thoroughly investigated.